Yield performance and anthocyanin content of several purple-fleshed sweet potato clones grown in two locations in East Nusa Tenggara, Indonesia - I G. B. ADWITA ARSA; YOSEP S. MAU; ANTONIUS S. S. NDIWA; Y. R. Y. GANDUT; LILY F. ISHAQ; I NYOMAN W. MAHAYASA (Society for Indonesian Biodiversity, 2024)
Abstract. Arsa IGBA, Mau YS, Ndiwa ASS, Gandut YRY, Ishaq LF, Mahayasa INW. 2024. Yield performance and anthocyanin content of several purple-fleshed sweet potato clones grown in two locations in East Nusa Tenggara, Indonesia. Biodiversitas 25: 2276-2289. Several promising purple-fleshed sweet potato hybrid clones were identified to have high yield potential and, thus, can be evaluated for other superior traits and later be further processed for varietal registration and release. This study aimed to determine the tuber yield performance and anthocyanin content of several purple-fleshed sweet potato clones across two locations and to identify the best clones based on mean performance and stability. The study was conducted in the farmer's field in two different altitudes in West Timor, i.e., Mata Air Village, Kupang District (86 masl) and Netpala Village, Timor Tengah Selatan (TTS) District (1,090 masl) from April to September 2023. Six purple-fleshed sweet potato clones/varieties were assigned as treatment. The experiment was laid out in a complete block design in each location, and each treatment consisted of three replicates. Observed data included fresh storage root yield, number of storage roots per plant, storage root length, storage root tuber diameter, and tuber anthocyanin content. Observed data from the two trial locations were subjected to a combined ANOVA, cluster analysis, Principal Component Analysis (PCA), and GGE biplot analysis. The results showed that the genotype-by-location interaction effect was significant in all studied traits. Meanwhile, location or genotype significantly affected all traits except for the location, which did not significantly affect the anthocyanin content. The storage root yield ranged from 19.95 t ha-1 to 49.33 t ha-1, while the anthocyanin content ranged from 28,64 mg/100 g to 157,65 mg/100 g. The ranks of the tested genotypes based on the mean performance and stability are Undana UJ 7>Undana UJ 1>JPV-1>Antin 3>Undana UJ 6>Undana UJ 3 for storage root yield and JPV-1>Antin 3>Undana UJ 7>Undana UJ 6>Undana UJ 3>Undana UJ 1 for anthocyanin content.